Damping Based Traffic Allocation in Wireless Machine-to-Machine Communications Networks - Ruiguo Yu; Zhenxia Yuan; Mankun Zhao; Mei Yu; Xu Lu (International Journal of Distributed Sensor Networks)
Machine-to-machine (M2M) technology that allows machine devices to communicate directly with each other without human intervention has emerged as a cutting-edge technology for next-generation communication. As its applications become more and more popular, the number of users grows quickly and the quality of service needs to be improved. The traffic allocation problem may lead to many other problems such as low utilization ratio of the bandwidth and the jitter. When we tried to analyze the load on different paths using the simplest multipath routing algorithms, we found that the load changes just like simple harmonic motion, which inspires us to use physic and mathematic methods and tools to analyze the loading balance problems. And then, we designed a new traffic allocation algorithm. Compared with other algorithms, the algorithm proposed in this paper has much wider applicability. And the performance comparison experiment shows that DBTAs can really achieve improvement in decreasing the packet delay variance.